Monitoring of black soldier fly, Hermetia illucens (L.) (Diptera: Stratiomyidae) population in semi-captive controlled conditions - Mohamad Ibrahim Mohamad Isa; Hadura Abu Hasan (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Hermetia illucens (Diptera: Stratiomyidae), or known as Black Soldier Fly (BSF), has lately been found in various regions of the world, including Malaysia. BSF has been linked to decomposing organic substances like animal manure or plant material. This species was discovered near poultry operations in Tasek Gelugor, Penang, Malaysia, and was then placed into semi-captive adult cages (2 m width × 4 m length × 2.5 m height) for colony establishment. For a period of 10 months, the population of this species was observed. The population of BSF increased but subsequently fluctuated over the months. Temperature and relative humidity were measured as well as the weight of BSF eggs. The association between climatic conditions and the weight of eggs was investigated using Spearman's correlation coefficient analysis. Kruskal Wallis test,